Financial Literacy and Human Capital Readiness among Vocational Students in Yogyakarta - Novi Diah Wulandari; Zulfatun Ruscitasari; Suroya 'Izzatul Mustafidah; Budi Sutiono (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: Preparing students for the workforce is a key priority in vocational education, requiring graduates to possess occupational skills, social competencies, personal development, and financial management abilities. Objective: This research investigates how self-efficacy, soft skills, and financial literacy contribute to work readinessamong vocational high school students in Yogyakarta, with self-confidence serving as an intermediary variable. Methods: This research adopted a quantitative approach through a cross-sectional survey administered to 348 vocational high school students. Analysis was carried out using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. Results: The results reveal that self-efficacy (β = 0.467, p < 0.001), soft skills (β = 0.201, p < 0.001), financial literacy (β = 0.193, p = 0.013), and self-confidence (β = 0.096, p = 0.042) positively predict work readiness (R² = 0.859). Notably, self-efficacy did not significantly influence self-confidence (β = −0.044, p = 0.565), suggesting that task-based capability beliefs do not automatically translate into social-evaluative confidence. Financial literacy had the strongest effect on self-confidence (R² = 0.813) and mediated the financial literacy–work readiness pathway (β = 0.076, p = 0.046). The indirect effect of soft skills through self-confidence was near-significant (p = 0.052) and should be interpreted cautiously. Conclusion: This study contributes to vocational education scholarship by revealing that financial literacy acts both as an independent determinant and as an antecedent of self-confidence, which subsequently boosts work readiness, whereas self-efficacy exerts its influence through a direct performance-oriented pathway rather than through a confidence-based mediating route.